Comparison of approaches to determine echocardiographic outcomes for children with latent rheumatic heart disease - Rwebembera, Joselyn; Beaton, Andrea; Okello, Emmy; Nakitto, Miriam; Pulle, Jafesi; Scheel, Amy; Grobler, Anneke; Steer, Andrew Craig; Sable, Craig (Open Heart, 2022)
Screening programmes using echocardiography offer opportunity for intervention through identification and treatment of early (latent) rheumatic heart disease (RHD). We aimed to compare two methods for classifying progression or regression of latent RHD: serial review method and blinded, side-by-side review.
Keywords: Latent Rheumatic heart disease; Comparison; Echocardiographic outcomes; Children